Analysis of The Interrelationship Between Employee's Digital Skills, Digitalization in Human Resource Management and Organizational Performance - Malini Lubis, Fatimah; Hegy Suryana, Alean Kistiani; Assery, Syeh; Lahuddin, Abdul Haris; Nurdiani, Tanti Widia (International Journal of Engineering, Science and Information Technology, 2024)
This study aims to provide knowledge about the influence of digital transformation, especially in the human resource management department, on organizational performance, especially in the hospitality industry. This study uses a combination of exploratory and descriptive approaches. This study collects data using structured observation and field surveys. The results of the study indicate that the hospitality industry is currently undergoing digital transformation in various departments and management requires support for digital mastery from all human resources working in the hospitality industry. Various skills and mastery of digital devices required by staff in the human resources department are communication skills, including the use of email, instant messaging applications, and applications in the selection and recruitment process. Other technological devices needed by hotel management are hotel management systems and office asset management. The advice given to hotel management is to provide training and certification for staff who work to address the existing skills gap. Another conclusion of this study is that employers view informational skills as complementary and not important during the employee selection process. The most sought-after position is a receptionist, which requires strong communication skills and efficient operational capabilities.